Gateway to electronic media services : an evaluative study of the digital library at the Nanyang Technological University. - Wong, Oi May. (2008)
The aim of this study is to examine whether the digital library at the Nanyang Technological University - Gateway to Electronic Media Services (GEMS) -- is able to facilitate effective access to information resources from the end-users' perspective.